2020
DOI: 10.7554/elife.55964
|View full text |Cite
|
Sign up to set email alerts
|

Automated task training and longitudinal monitoring of mouse mesoscale cortical circuits using home cages

Abstract: We report improved automated open-source methodology for head-fixed mesoscale cortical imaging and/or behavioral training of home cage mice using Raspberry Pi-based hardware. Staged partial and probabilistic restraint allows mice to adjust to self-initiated headfixation over 3 weeks’ time with ~50% participation rate. We support a cue-based behavioral licking task monitored by a capacitive touch-sensor water spout. While automatically head-fixed, we acquire spontaneous, movement-triggered, or licking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 60 publications
(144 reference statements)
0
44
0
Order By: Relevance
“…For instance, it is poorly understood whether differences in training trajectories result in different cognitive strategies or neural representations in a task (e.g., Latimer and Freedman, 2019). Standardization and automation in animal training may aid experimental investigation of task shaping effects (Murphy et al, 2020;Berger et al, 2018). PsychRNN provides an accessible framework to explore neuroscientific questions related to task shaping in RNN models.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is poorly understood whether differences in training trajectories result in different cognitive strategies or neural representations in a task (e.g., Latimer and Freedman, 2019). Standardization and automation in animal training may aid experimental investigation of task shaping effects (Murphy et al, 2020;Berger et al, 2018). PsychRNN provides an accessible framework to explore neuroscientific questions related to task shaping in RNN models.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is poorly understood whether differences in training trajectories result in different cognitive strategies or neural representations in a task (e.g., Latimer and Freedman, 2019). Standardization and automation in animal training may aid experimental investigation of task shaping effects (Murphy et al, 2020;Berger et al, 2018). Although…”
Section: Discussionmentioning
confidence: 99%
“…A large part of the appeal of these computers is the vast array of external devices (i.e., sensors or motors) that can be connected and controlled through the GPIO ports. Devices for operant conditioning (Longley et al, 2017;Mazziotti et al, 2020), conditioned place preference (Vassilev et al, 2020), head-fixed mesoscale cortical imaging (Murphy et al, 2020), and even virtual reality (Tadres & Louis, 2020) have been reported. Further, a wide range of environmental factors (e.g., humidity, barometric pressure, and light) can be monitored using Raspberry Pi (Longley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%